2016
DOI: 10.1161/strokeaha.116.013003
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytopenia Is an Independent Predictor of Unfavorable Functional Outcome in Spontaneous Intracerebral Hemorrhage

Abstract: Background and Purpose— Stroke-associated immunosuppression is an increasingly recognized factor triggering infections and thus potentially influencing outcome after stroke. Specifically, lymphocytopenia after intracerebral hemorrhage (ICH) has only been addressed in small-sized retrospective studies of mixed intracranial bleedings. This cohort study investigated the natural course of lymphocytopenia, parameters associated with lymphocytopenia on admission (LOA) and during stay, and evaluated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Because previous reports have demonstrated that the relationship between total lymphocyte count and susceptibility to infections is not linear and that the odds of experiencing an IC increase only when the lymphocyte count drops below a critical threshold [7, 12], we analyzed admission lymphopenia (AL) defined as absolute lymphocyte count < 1000/µL [7, 13]. We also collected data on admission leukopenia (absolute leukocyte count < 4000/µL), admission neutropenia (absolute neutrophil count < 1500/µL), and admission monocytopenia (absolute monocyte count < 200/µL) [14, 15].…”
Section: Methodsmentioning
confidence: 99%
“…Because previous reports have demonstrated that the relationship between total lymphocyte count and susceptibility to infections is not linear and that the odds of experiencing an IC increase only when the lymphocyte count drops below a critical threshold [7, 12], we analyzed admission lymphopenia (AL) defined as absolute lymphocyte count < 1000/µL [7, 13]. We also collected data on admission leukopenia (absolute leukocyte count < 4000/µL), admission neutropenia (absolute neutrophil count < 1500/µL), and admission monocytopenia (absolute monocyte count < 200/µL) [14, 15].…”
Section: Methodsmentioning
confidence: 99%
“…Many thanks, and here we express our best sincere respect to Giede-Jeppe et al 1 for their innovative and interesting study.…”
mentioning
confidence: 77%
“…We would like to highlight 3 important issues raised in the study by Giede-Jeppe et al 1 First, why does the number of circulating lymphocytes decrease in patients with ICH? Two major reasons come to mind: one has to do with the severity and progression of ICH, and the second reason is related to some external environment factors, such as infections that can potentially change lymphocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations